Calibration and Calculation of Polarization Lidar. Issue 7 (12th July 2019) - Xian, Jinhong; Sun, Dongsong; Xu, Wenjing; Tian, Chongguo; Tan, Qingzhi; Han, Yuli; Yang, Shaochen
Abstract: Although polarization lidar technology has been widely used to detect depolarized particles, many difficulties still exist in measuring accurate values for the depolarization ratio. This ratio is basically related to the difference between the optical and the electronic gain of the lidar's channels, the polarization purity of the laser pulse, and the error in the alignment between the laser's polarization plane and the polarizer. We propose here an algorithm for the calibration and calculation of polarization lidars. Numerical simulations showed that the depolarization ratio profile retrieved from the proposed algorithm agrees well with the simulated profile. The proposed algorithm no longer requires the laser source to be linearly polarized. Instead, the light polarization can be elliptical or random. During the installation process, the polarization of the detector is no longer required to be parallel or perpendicular to the polarization direction of the laser source and can be done in any direction. Key Points: An algorithm was proposed to retrieve the depolarization ratio from polarization lidar data The algorithm no longer requires the laser source to be linearly polarized, allowing for elliptical or random polarization to be used The polarization of the detector is no longer required to be parallel or perpendicular to the polarization plane of the laser source